CO2 capture and conversion using graphene-based materials: a review on recent progresses and future outlooks - Mutawakkil Isah; Ridhwan Lawal; Sagheer A. Onaizi (Green Chemical Engineering)
Rapidly increasing global atmospheric carbon dioxide (CO2) concentration poses a serious threat to life on Earth. Conventional CO2 capture methodologies which rely on using sorbents to capture CO2 from point sources while effective in curbing the rate of CO2 increase, fall short of achieving net reduction. The last decade has witnessed a surge in the development of chemical sorbents cycled through adsorption-desorption processes for CO2 extraction from low-concentration sources like air (e.g., Direct Air Capture (DAC)). However, the efficiency of these technologies hinges on the creation of next-generation materials. Graphene, a revolutionary material discovered about two decades ago, offers great promise for CO2 capture and conversion. This single-atom-thick sheet of sp2-hybridized carbon atoms has unique and tuneable properties, solidifying its position as the most extensively studied nanomaterial of the 21st century. This review provides a comprehensive overview of the developing field of graphene-based materials for CO2 capture and conversion. The discussion begins with an exploration of the synthesis techniques for graphene and the integration of foreign elements to tune its properties for targeted applications. Subsequently, the review discusses the utilization of graphene and its derivatives in both CO2 capture and conversion processes, encompassing photocatalytic and electrocatalytic conversion methods. Despite the immense potential, the practical implementation of graphene-based DAC necessitates further exploration and development. Notably, engineering efficient of graphene-air interfacial contact is paramount to expediting the deployment of DAC as a viable strategy for mitigating climate change. The review concludes by highlighting gaps for future research to tackle challenges in this critical area of environmental pollution mitigation.